Education Dynamics Amid Economic Crisis: Access, Quality, Prosperity Through Policy, Society - Adi Putra; Abd Haris; Lizabeth Sari Dewi; Aulia Yunicha Harly (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
In this extensive study, we thoroughly analyzed educational dynamics within the context of an economic crisis, primarily focusing on the intricate interplay among social, economic, and policy factors. Our research aimed to understand how these factors intersected and collectively influenced educational access, quality, and well-being during economic turmoil. The research methodology encompassed a comprehensive review of existing literature, empirical data collection through surveys and interviews, and quantitative analysis of educational outcomes across diverse economic conditions. Policy interventions were pivotal in shaping education's response to the economic crisis. Targeted measures, such as increased funding for low-income schools and initiatives supporting educators, proved effective in mitigating the adverse effects of economic downturns on education. Qualitative data underscored the invaluable role of social capital and community resilience in supporting education during challenging times. Communities with active social networks and robust community organizations supported students and educators. Our findings unveiled a multifaceted landscape marked by both challenges and opportunities. Notably, the economic crisis disproportionately impacted marginalized populations, leading to widening disparities in educational outcomes. Access to educational resources was severely disrupted, particularly in disadvantaged regions, exacerbating pre-existing inequalities. Moreover, the psychological well-being of students and educators emerged as a crucial aspect of educational quality, with rising stress and anxiety influencing the learning environment.